2018
DOI: 10.1136/bmjopen-2017-020923
|View full text |Cite
|
Sign up to set email alerts
|

Public subsidies and the recommendation of child vaccines among primary care physicians: a nationwide cross-sectional study in Japan

Abstract: ObjectiveAlthough public subsidies and physician recommendations for vaccination play key roles in increasing childhood vaccination coverage, the association between them remains uncertain. This study aimed to identify the association between awareness of public subsidies and recommendations for Haemophilus influenzae type b (Hib), Streptococcus pneumoniae (pneumococcal conjugate vaccine (PCV)) and human papillomavirus (HPV) vaccinations among primary care physicians in Japan.DesignThis is a cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, a paradox existed in our results, that is, the range of the working years after graduation was positively associated with the administration of voluntary mumps vaccine for adults but negatively associated with the recommendation of voluntary mumps vaccine for children. Sakanishi et al reported generation‐specific gaps regarding vaccination recommendation in 2012, which described PCPs working 3–10 years after graduation as more disposed to recommended Haemophilus influenza type b vaccine, seven‐valent pneumococcal conjugate vaccine, and human papillomavirus vaccine than PCPs working 11–40 years after graduation 14 . On the other hand, PCPs with a higher postgraduate year may generally have a greater interest in mumps vaccines at the present study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, a paradox existed in our results, that is, the range of the working years after graduation was positively associated with the administration of voluntary mumps vaccine for adults but negatively associated with the recommendation of voluntary mumps vaccine for children. Sakanishi et al reported generation‐specific gaps regarding vaccination recommendation in 2012, which described PCPs working 3–10 years after graduation as more disposed to recommended Haemophilus influenza type b vaccine, seven‐valent pneumococcal conjugate vaccine, and human papillomavirus vaccine than PCPs working 11–40 years after graduation 14 . On the other hand, PCPs with a higher postgraduate year may generally have a greater interest in mumps vaccines at the present study.…”
Section: Discussionmentioning
confidence: 52%
“…If local governments subsidize voluntary mumps vaccination for children, the economic burden will be lower for vaccine recipients, making it easier for PCPs to recommend the vaccine. Subsidies also have the potential to improve vaccination rates 14,23 . The Japanese government subsidized the measles–rubella vaccine for a catch‐up campaign during a measles outbreak from 2008 to 2013 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Tolunay et al (2014), it was determined that the physicians who did not recommend the vaccine indicated the cost as the primary reason. In addition, in the study conducted by Sakanishi et al (2018) in 2012 in Japan, it was determined that primary care physicians recommended the HPV vaccine at a frequency of 58.1%. In a study conducted with tertiary healthcare professionals, 80.2% of the participants were aware of the existence of the HPV vaccine, but only 30.5% stated that they or a relative had the HPV vaccine.…”
Section: Hpv Vaccinementioning
confidence: 99%
“…Thus, it is important for physicians to have accurate knowledge regarding vaccination to increase vaccine administration or recommendation rates 20–22. In Japan, the HPVv is administered not only by paediatricians, obstetricians and gynaecologists (OBGYNs), but also by primary care physicians (PCPs) 23 24. A 2012 nationwide survey on practices and attitudes towards vaccination among PCPs in Japan23 24 showed that the proportion of PCPs administering and actively recommending HPVv was 58.3% and 46.5%, respectively 23.…”
Section: Introductionmentioning
confidence: 99%